Bioactivities and formation/utilization of soluble microbial products (SMP) in the biological sulfate reduction under different conditions. (April 2019) - Qian, Jin; Zhou, Junmei; Pei, Xiangjun; Zhang, Mingkuan; Liu, Yu
Abstract: The biological sulfate reduction (BSR) plays a critical role in the organic compound removal in the sulfur bioconversion-associated sewage treatment process. The soluble microbial products (SMP) are the major components of residual organic compounds in the secondary treatment effluent and its presence directly affects treatment capacity. In addition, the SMP could be one of the available organic substrates and be utilized as an electron donor in the bioreactions. However, the SMP formation and utilization in the BSR are poorly understood. Herein, the BSR activities and SMP generation/utilization were simultaneously investigated under different conditions, i.e. pH, temperature and ratio of organic carbon (C) to sulfur (S). The role of SMP as the electron donor for BSR was also identified. The higher BSR activities and rapid SMP synthesis were found under neutral and alkaline conditions, but the SMP utilization as the electron donor is not favorable at pH 7.0. The BSR activity became higher and more SMP was synthesized by raising the temperature. The ratio of C to S rarely affected the sulfidogenic activity but has an effect on the net SMP generation (total SMP generation – SMP consumption by SBR as the electron donor). The lower ratio of C/S could result in the low residual SMP level in the reactor. And the SMP-induced BSR activity was higher under the acid and alkaline conditions compared with the neutral condition. Graphical abstract: Image 1 Highlights: Bioactivity and SMP generation/utilization in SO4 2− reduction were studied. Higher temperature enhanced SO4 2− reduction activity and SMP generation. Low SMP residue and high bioactivity were achieved under SO4 2− sufficient condition. SMP could be utilized as an electron donor for SO4 2− reduction. SMP-induced BSR activity was lower under neutral condition.